Vigabatrin Associated Retinal Pathology - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A prospective study of 29 children treated with vigabatrin (VGB) as add on therapy for epilepsy included ophthalmic examination before and at 6-month intervals for 6.5 years, at Sultan Qaboos University Hospital, Sultanate of Oman.